L’atelier théâtral en philologie romane : sources d’inspiration, organisation, agir enseignant - Blachowska-Szmigiel, Marzena (Studia Romanica Posnaniensia, 2017)
The purpose of this paper is to present theatre workshops as a tool for reducing the linguistic anxiety of students and supporting the development of linguistic competence, discourse competence, personal and interpersonal competence in the context of teaching and learning French as a foreign language at the Romance philology. As a first step, we look at the sources of inspiration and the approach, mission, objectives and conditions of the theatre workshop, then we go on to briefly describe how it works and, finally, we concentrate on the challenges of the Teaching act.